Fınansal krızlerin Balkan ülkeleri ve Türkiye’deki e-sigortacılık üzere etkilerinin karşılaştırılması - Drpljanin, Belma (My University, 2015)
FINANSAL KRIZLERİN BALKAN ÜLKELERİ VE TÜRKİYE’DEKİ E-SİGORTACILIK ÜZERE ETKİLERİNİN KARŞILAŞTIRILMASI Bu çalışmanın amacı, Balkan ülkeleri ve Türkiye'de elektronik güvenlik gelişimini vurgulamak ve onun sigorta, elektronik sigorta ve finansal krizin teorik olarak mali kriz koşullarında karlı kullanımını olanağını açıklamaktadır. Bu eser üç bölümden oluşmaktadır. İlk bölümde sigortanın teorik kavramı anlatılmaktadır. Sigortanın teorik kavramını gözden geçırmek şu şekilde mümkündür: sigorta sözleşmesini, sigorta sınıflandırmalarını, riskin ayrılmaz kavramını ve sigorta riskinin sınıflandırılmasının analize etmektedir. Özel vurgu elektronik sigorta üzerindedir. Aynı zamanda elektronik sigortanın gelişimindeki mevcut eğilimlerine bir bakış verilmiştir. Finansal krizin elektronik sigortanın gelişim akımlarını etkilediği gibi, ayrıca tarihsel gelişimine ve kriz kavramına dikkat çekmektedir. Yani onun özünün anlaşılması ve sigorta piyasasını özellikle elektronik sigortasını hangi şekilde etkilemektedir. İkinci bölümde, Balkan ülkeleri ve Türkiye'de elektronik sigortanın gelişimine finansal krizin etkilerini detaylı anlatılmaktadır. Bu ülkelerde elektronik sigortanın işlemesi, mevcut olan aşamaları, gelişim eğilimleri, elektronik sigortanın kullanımının şekli ve onun temel kayramları analize edilmiştir. Mevcut durumun daha iyi tanıtılması ve mali krizin elektronik sigorta üzerindeki etkilerini göstermek için sayısız örnekler ve istatistikler sunulmuştur. Son olarak, üçüncü bölümde, Balkan ülkeleri ve Türkiye'de mali krizde elektronik sigortanın karlı kullanımı için bir çok pratik öneri sunulmuştur.

The aim of this study is to indicate the development of electronic insurance in the countries of Balkan and Turkey, as well as to indicate the possibility of its profitable usage under the conditions of financial crisis, on the theoretical basis of insurance, electronic insurance and financial crisis. This thesis consists of three parts. The first part presents the theoretical concept of insurance. Overview of the theoretical concept of insurance is possible through the overview of the concept of insurance through analyzing the insurance contract, insurance classifications, inseparable concept of risk and classification of insurance risk. Special emphasis is on the electronic insurance, as a contemporary direction of the development of insurance, from general information and types of the electronic insurance to analyzing markets of Turkey and the Balkans, regarding the development of the electronic insurance. It also gives an overview of the current trends in the development of the electronic insurance, or of prevailing directions of the development of the electronic insurance. As the financial crisis has inevitably affected the directions of such flows of the development of the electronic insurance, special attention is paid to its historical development, to the concept of crisis, or to the overview of its essence and the ways it affects the insurance market, in particular the electronic insurance. In the second part is presented the detailed impact of the financial crisis on the development of the electronic insurance in the Balkans and in Turkey. Analyzed is the functioning of the electronic insurance in these countries, the stages in which it is currently stated, as well as the tendencies of its development, the method of usage of the electronic insurance, together with the basic features. In terms of better demonstration of the current state and real impact of the financial crisis on the electronic insurance, presented are numerous examples and statistics. Lastly, in the third part are offered practical recommendations for profitable usage of the electronic insurance under the conditions of financial crisis in the countries of Balkan and Turkey.
Keywords: Bankacılık; Sigortacılık; Türkiye